The business of sustainable tourism development and management - Slocum, Susan L.; Aidoo, Abena; McMahon, Kelly 1969- (Abingdon, Oxon New York, NY Routledge, 2020)
"The Business of Sustainable Tourism Development and Management provides a comprehensive introduction to sustainable tourism, crucially combining both theoretical and practical approaches to equip students with the tools to successfully manage a sustainable tourism business or destination. Covering a range of crucial topics such as mass tourism, alternative tourism, human capital management and many more, this book incorporates a global curriculum that widens the sustainable tourism debate to include theoretical perspectives, applied research, best-practice frameworks, business tools, and case studies, facilitating a more comprehensive sustainable tourism educational strategy. Information on how to effectively implement strategies that can be applied to business environments, entrepreneurship, and job skills to enhance career preparation is at the forefront of this textbook. Highly illustrated and with an interactive companion website including bonus learning materials, this is the ideal textbook for students of tourism, hospitality, and events management at both undergraduate and postgraduate levels"-- Provided by publisher.
Introducing sustainable tourism -- Understanding capital -- Globalization, localism, and sustainability -- Governance of sustainable tourism -- The sustainable traveler -- Mass tourism -- Alternative tourism -- Marketing for sustainability -- Supply and value chain management -- Certification -- Human capital management -- Visitor management -- The future of sustainable tourim.
Includes bibliographical references and index.
Susan L. Slocum is an Associate Professor in the Department of Tourism and Event Management at George Mason University, Manassas, Virginia. Abena Aidoo is an Associate Professor in the Tourism and Events Management Program at George Mason University, Fairfax, Virginia. Kelly McMahon is a business professional with 18 years in the high-tech industry creating and leading high-performing global teams.
Keywords: Sustainable tourism; Tourism -- Management